An Efficiency of Auxiliary Power Consumption in Substations Using Renewable Energy Potentials in East Kalimantan Province - Silalahi, Chandra Lima; Setiawan, Eko Adhi (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2025)
PT PLN (Persero) as the Indonesian state electricity supply company must carry out an energy transition in terms of generation, transmission and distribution. Substation in Indonesia’s electric power transmission sector have not yet incorporated the idea of green energy into their operation, despite the fact that there is a great potential for renewable energy in substations, such as the usage of solar and wind energy. The primary power source for the auxiliary substation is energy from the grid, with diesel power serving as a backup. However, the energy mix in the Kalimantan grid is still dominated by energy from coal (based on the Annual Operation Evaluation Report PLN UIP3B 2023). This research investigates the technical and economic viability of utilizing renewable energy in auxiliary substations to mitigate the company’s escalating financial burden. Technically, the study aims to determine the optimal PV panel capacity required for auxiliary power needs. Economically, it evaluates the total investment and operational costs, Internal Rate of Return (IRR), Return on Investment (ROI), payback periods, and Levelized Cost of Energy (LCOE). Unique to this study is the direct measurement of kWh consumption data from 23 substations in East and North Kalimantan, a method not previously employed. The findings provide recommendations on the appropriate PV capacity for installation in substations and present economic analysis.